Against All Odds Women’s Ways to Mathematical Research Since 1800 - Kaufholz-Soldat, Eva; Oswald, Nicola M.R (Women in the History of Philosophy and Sciences, 2020)
XXI, 319 p. 21 illus., 10 illus. in color.